Geochemical controls on invisible gold fixation in arsenian pyrite: Evidence from the Western Mecsek and Bakyrchik deposits - Medet Junussov; Maxat K. Kembayev; Akmaral Baisalova; Manshuk Kokkuzova; Yerkhozha Mamanov; Gulnur Mekenbek; Salima Cherkeshova (Acta Geochimica, 2026)

Intensified wildfire activity due to volcanism across the Triassic-Jurassic boundary in northwestern China - Wenxin Hu; Qingyong Luo; Jianfa Chen; Linhao Fang; Man Lu; Medet Junussov; Tao Du; Xintong Liu; Xiaohang Pan; Gui Wang; Fangchao Yan (International Journal of Coal Geology, 2026)

Exploring rare earth elements in Northern Kazakhstan: The potential of ion-adsorption clays and coals as unconventional sources - Medet Junussov; Maxat K. Kembayev; Manshuk Kokkuzova; Akmaral Baisalova; Zamzagul T. Umarbekova; Rustem Abirov; Sayat Erbolatuly Rais; Abylay Amantayev (Acta Geochimica, 2025)

Four decades of trends in invisible gold research: a web of science-based bibliometric analysis (1985–2024) - Medet Junussov; Maxat K. Kembayev; Gulnur Mekenbek; Nessipzhan Mukhamediyarova; Manshuk Kokkuzova; Aizada Assambayeva; Rustem Abirov (Earth Science Informatics, 2025)

Trace element geochemistry of dispersed organic matter in Western Mecsek uranium ore deposit, Southern Hungary - Medet Junussov; Maxat Kembayev; Nessipzhan Mukhamediyarova; Murat Maratuly Rustembekov; Rustem Abirov (Acta Geochimica, 2025)

Organic petrography and geochemistry of the Lower-Carboniferous coals from the Ekibastuz Basin, Kazakhstan - Majid Safaei-Farouji; David Misch; Reinhard F. Sachsenhofer; Johannes Weitz; Ivan Kojic; Ksenija Stojanović; Serik Tursyngaliyev; Medet Junussov; Milovan Fustic (International Journal of Coal Geology, 2025)

Geochemical analysis of organic matter associated with gold in ore deposits: A study of Kazakhstan and Hungary - Medet Junussov; Asif Mohammad; Sotirios Longinos (Acta Geochimica, 2025)

Preliminary analysis on roles of metal–organic compounds in the formation of invisible gold - Medet Junussov; Mádai Ferenc; Kristály Ferenc; Tóth Tivadar; Fintor Krisztián; Muránszky Gábor; Prekob Ádám; Hámor-Vidó Mária (Acta Geochimica, 2021)
The paper comprises new analytical data on the nature and occurrence of gold in solid pyrobitumen, closely associated with the main gold-bearing sulfide arsenic ores of the Bakyrchik gold deposit (Kazakhstan), related to post-collisional magmatic-hydrothermal origin. Gold mineralization of the deposit occurs mainly in the form of an “invisible” type of gold in the structures of arsenian pyrite and arsenopyrite, and the form of gold-organic compounds of pyrobitumen in carbonaceous-terrigenous sequences of Carboniferous formation. Microscopic and electron microscopic analysis, Raman and FT-Infrared analysis, mineralogical and three-step sequential extraction analysis (NH 2 OH·HCl, H 2 O 2, HNO 3 + HCl) has been carried out using 9 ore samples (from 3 different types of ores) for a comprehensive study of pyrobitumen and sulfide arsenic ores focusing mainly on organic matter. The sequentially extracted precious metal content of pyrobitumen reaches up to 7 ppm gold and other metals like Ag 4 ppm, Pt 31 ppb, and Pd 26 ppb, forming metal–organic compounds, while arsenic sulfide minerals incorporate 11 ppm gold, 39 ppm Ag, 0.49 ppm Pt. The enrichment of gold associating with organic matter and sulfide ore minerals was confirmed in this study. Organic matter was active in the migration of gold and the capture of gold by pyrobitumen. Moreover, the reductive organic matter agent released gold, most likely for the sulfide arsenic ore minerals. Pyrobitumen was a decisive factor in the concentration, transportation, and preservation of gold in the deposit.